Impact of an electronic consultant system on hypersensitivity reactions to iodinated radiocontrast media: an observational study. Issue 1074 (3rd March 2015) - Yang, Min-Suk; Choi, Sang-Il; Song, Woo-Jung; Kim, Sae-Hoon; Kang, Hye-Ryun; Park, Heung-Woo; Cho, Sang-Heon; Min, Kyung-Up; Kim, Jae-Hyoung; Chang, Yoon-Seok
ABSTRACT: Objective: To evaluate the impact of an electronic consultation support system on the incidence of hypersensitivity reactions to iodinated radiocontrast media (RCM). Materials and methods: A retrospective observational study was conducted before and after the introduction of the consultation support system. The 1-year study period was divided into two 6-month periods: before and after 1 December 2012 (baseline and intervention periods, respectively), which was when our consultation support system was introduced. Data from examinations were collected retrospectively from the hospital information centre and problem reporting sheets in the radiology department. The primary outcome was the incidence of RCM reactions before and after the introduction of the consultation support system. Generalised estimating equations were used to account for the correlation between the same patients measured on multiple occasions. Results: There were 317/20 179 (1.6%) and 186/19 873 (0.9%) hypersensitivity reactions during the baseline and intervention periods, respectively. The consultation support system significantly decreased the odds of the occurrence of a RCM reaction (OR=0.59, 95% CI 0.49 to 0.71, p<0.001) compared with baseline. There was also a twofold increase in the premedication rate after initiation of the consultation support system (OR=2.05, 95% CI 1.16 to 3.65 p=0.01). However, there was no significant difference in the recurrence rate between the periods (OR=0.97, 95% CI 0.58 to 1.65, p<0.93). Conclusions: The introduction of the consultation support system reduced the incidence of hypersensitivity reactions to RCM and increased the use of premedication in patients with known hypersensitivity to RCM.